PENGARUH MEDIA VISUAL TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SISWASEKOLAH DASAR - Siswana, Lina; Halidjah, Siti; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to analyze the effect of visual media usage on writing skill of narrative essay on fifth grade students of Madrasah Ibtidaiyah Negeri Bangka Belitung Pontianak Tenggara. The method used in this research is quasi experimental design type nonequivalent control group design. The subjects of this research were all fifth grade students of Madrasah Ibtidaiyah Negeri Bangka Belitung Pontianak Tenggara academic year 2017/2018 which amounted to 70 students in which 35 VA students as control class and 35 VB students as experimental class. The research instrument used is a matter of writing skill test. Based on the result of research, the average of post-test result of control class is 77,77 and the average of post-test result of experiment class is 81,71 obtained tcount is 1,9696 and ttable (Î± = 5%) is 1,6693, which means tcount> ttable, then Ha is accepted. So, it can be concluded that there is effect of using visual media. Based on the calculation of effect size (ES) obtained 0,52 (medium criterion). This means the visual media usage has a moderate effect on the writing skill of narrative essay on fifth grade students of Madrasah Ibtidaiyah Negeri Bangka Belitung Pontianak Tenggara.Â Keywords : Effect, visual media, writing skill, narrative essay